2009
DOI: 10.2135/cropsci2008.06.0371
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Isolines of Cotton Differing in Fiber Color for Yield, Quality, and Photosynthesis

Abstract: Naturally colored cotton (Gossypium hirsutum L.) fibers (CCFs) are eco‐friendly for the textile industry because they omit the dyeing process and reduce harmful effluent liquor. However, the low yield and quality of CCFs have greatly affected their development. Limited information is available on the reasons for the low yield and quality of CCFs. The aim of this 2‐yr investigation was to compare variations in chlorophyll concentration, net photosynthesis rate, monosaccharide concentration, and fiber yield and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
(54 reference statements)
0
28
0
1
Order By: Relevance
“…Cellulose is the major component of cotton fibre and high amounts of cellulose always guaranteed a better quality of cotton fibre (Martin & Haigler 2004). In the present study, the amount of cellulose was lower in coloured cotton fibres compared to white cotton fibre, and might be due to flavonoid synthesis (Dutt et al 2004;Hua et al 2007Hua et al , 2009. However, a significantly higher amount of cellulose after 15 DPA in the interspecific coloured cotton hybrid as compared to their parental lines suggested the accumulation of dominant alleles at different loci for cellulose synthesis.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…Cellulose is the major component of cotton fibre and high amounts of cellulose always guaranteed a better quality of cotton fibre (Martin & Haigler 2004). In the present study, the amount of cellulose was lower in coloured cotton fibres compared to white cotton fibre, and might be due to flavonoid synthesis (Dutt et al 2004;Hua et al 2007Hua et al , 2009. However, a significantly higher amount of cellulose after 15 DPA in the interspecific coloured cotton hybrid as compared to their parental lines suggested the accumulation of dominant alleles at different loci for cellulose synthesis.…”
Section: Discussionmentioning
confidence: 40%
“…However, cultivation of coloured cotton has not accelerated accordingly (Dutt et al 2004). The fibre quality and yield of coloured cotton are inherently inferior to white cotton fibre (Murthy 2001; Wang & Li 2002a;Li et al 2004;Hua et al 2009;Yuan et al 2010), so cotton breeders continue to be engaged in producing coloured cotton genotypes with high yield and good fibre quality using heterosis breeding (Basu 1996). Previously, interspecific as well as intraspecific heterosis has been reported in coloured cotton with an average increase of 18% in agronomic-and yieldrelated traits (Meredith & Bridge 1972;Dutt et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the overexpression of the F3H gene has no effect on cotton fibre length. This experiment has shown that flavonoid metabolism could be associated with fibre pigmentation and quality (Dutt et al, 2004;Hua et al, 2009;Feng et al, 2015;Hande et al, 2017).…”
Section: Geneticsmentioning
confidence: 88%